A GARCH APPROACH TO VaR CALCULATION IN FINANCIAL MARKET - Nurfadhlina Abdul Halim; Endang Soeryana; Alit Kartiwa (International Journal of Quantitative Research and Modeling, 2020)
Value at Risk (VaR) has already becomes a standard measurement that must be carried out by financial institution for both internal interest and regulatory. VaR is defined as the value that portfolio will loss with a certain probability value and over a certain time horizon (usually one or ten days). In this paper we examine of VaR calculation when the volatility is not constant using generalized autoregressive conditional heteroscedastic (GARCH) model. We illustrate the method to real data from Indonesian financial market that is the stock of PT. Indosat Tbk.